Dynamics of violations the absorption function of the small intestine in conditions of acute blood loss complicated by ischemia-reperfusion of the limbs and their correction - Strelbytska, I.; Hudyma, A. (Journal of Education, Health and Sport, 2021)
Introduction. In the structure of modern injuries in wartime and peacetime the share of gunshot wounds increased significantly. The timeliness of applying a tourniquet is one of the main methods of saving lives on the battlefield. The patterns of formation of enteral insufficiency syndrome in conditions of acute blood loss complicated by ischemia-reperfusion of the limb have not been studied enough. There are no data on the features of violations of the absorption function of the small intestine in these conditions and the effectiveness of correction with Carbacetam, which is able to reduce the manifestations of acute hemic hypoxia and ischemic-reperfusion syndrome. The objective of research: To establish the peculiarities of the absorption function of the small intestine in the pathogenesis of acute blood loss, ischemia-reperfusion of the limb and their combination. To evaluate the effectiveness of Carbacetam in the correction of identified abnormalities. Materials and methods. The experimental studies were conducted on 108 white nonlinear male rats weighing 200-220 g, which were housed in standard vivarium conditions. All animals were divided into five groups: control and four experimental. Under thiopental-sodium anesthesia in the first experimental group was simulated ischemia-reperfusion of the limb, in the second group – acute blood loss, and in the third group – these injuries were combined. In the fourth experimental group, animals with acute blood loss and ischemia-reperfusion of the limb were intraperitoneally administered Carbacetam at a dose of 5 mg per kilogram of animal weight. After 1 and 2 hours, as well as after 1, 7 and 14 days studied the absorption function of the intestines by D-xylose test. The results and discussion. Simulation of limb ischemia-reperfusion compared with the control group causes a decrease in the content of D-xylose in the urine after 1 day of the reperfusion period. Also, acute blood loss is accompanied by a significant decrease in this indicator after 1 day. Until the end of the experiment the rate increases, but up to 14 days does not reach the level of control. The combination of acute blood loss and ischemia-reperfusion of the limb causes a decrease in the content of D-xylose in the urine starting from 1 hour of the experiment, which reaches a minimum after 1 day and remains at the same level until 14 days. In these terms the rate was the lowest compared to other studied groups. The use of Carbacetam for corrective purposes in rats with acute blood loss complicated by ischemia-reperfusion of the limb, compared with animals without correction significantly reduces the detected abnormalities after 7 days and more after 14 days of use. Conclusions. Complications of acute blood loss by ischemia-reperfusion of the limb causes a significant decrease in the absorption function of the small intestine after 1 day of the experiment. The intensity of disorders was significantly higher compared to other experimental groups. The use of Сarbacetam for 7-14 days in the reperfusion period in animals with acute blood loss complicated by limb ischemia-reperfusion, compared with animals without correction, causes a significant increase in the absorption function of the small intestine. This indicates the protective effect of the drug under the conditions of simulated pathology.